KARAKTERISTIK WISATAWAN BACKPACKER DAN DAMPAKNYA TERHADAP PARIWISATA KUTA, BALI - Menuh, Ni Nyoman (Jurnal Master Pariwisata (JUMPA); Volume 02, Nomor 02, Januari 2016DO - 10.24843/JUMPA.2016.v02.i02.p11)
The study investigates the characteristics of backpacker tourists in terms of socio demographic, socio-geographical, and sociopsychographic in Kuta, Bali. It also discusses the impacts of backpacker tourists to tourism development in terms of socioeconomic, socio-cultural and environmental aspects in the tourist destination of Kuta Bali. Combining the quantitative and qualitative approaches, this study used 272 respondents who represented the characteristics of foreign backpacker tourists, and respondents from the circle of businessmen, property  managers, local communities and community leaders to determine the impacts of the presence of backpacker tourists to tourism industry in Kuta. The research findings shows that the characteristics of backpacker tourists are mostly young Europeans with professional jobs and have a high  income. Backpacker tourists’ arrivals not only bring the positive social, economic and cultural impacts but also negative environmental impacts. Some local people felt annoyance of the presence of backpacker tourists.
Keywords: backpacker tourists, tourist characteristics, tourist impacts, community response.